Implementation of Audio Visual Multimedia-Based Teaching Materials Using a Contextual Approach in Learning Writing Skills - Eni Karyati; Iis Ristiani (Raja Zulkarnain Education Foundation, 2025)
This study aims to describe: 1) students' responses to the implementation of teaching materials for procedural text writing skills based on audiovisual multimedia using a contextual approach; 2) learning outcomes for procedural text writing skills in audiovisual multimedia-based learning using a contextual approach. This study uses a quantitative descriptive approach. The study took place in the even semester of the 2024/2025 academic year at SDN Sukahurip. The population of this study was 21 fifth-grade students who took the pre-test, and took part in learning procedural text writing skills using audiovisual multimedia-based teaching materials containing a contextual approach and took the post-test. Student response data to the learner were collected using a closed questionnaire. Pre-test and post-test data for procedural text writing skills were collected through a performance test instrument that met the content validity requirements. Another instrument in this study was the lesson plan for learning procedural text writing skills using audio-video-based teaching materials. Pre-test and post-test data were analyzed using descriptive statistics, namely frequency and percentage. Data on the effectiveness of teaching materials for procedural text writing skills were analyzed using descriptive statistics, namely frequency, percentage, and mode. The results of the study: 1) students' responses to the implementation of teaching materials for writing procedural texts based on audiovisual multimedia using a contextual approach were categorized as positive, namely good; 2) as many as 5 students (23.80%) obtained procedural text writing skills classified as very good, 13 students (61.90%) in the good category, and 3 students (14.30%) in the sufficient category.